The Impact of Excluding Food Guarding from a Standardized Behavioral Canine Assessment in Animal Shelters - Mohan-Gibbons, Heather (Animals (Basel), 2018)
SIMPLE SUMMARY: Recent research has called into question the value of the food guarding assessment as a predictive tool for determining the safety of shelter dogs. This study examined the effect of eliminating the food guarding assessment in nine U.S. animal shelters. It was found that when the food guarding assessment was removed, bites or other injuries to staff or adopters did not increase. However, dogs exhibiting food guarding behavior were less likely to be adopted, had a longer shelter stay, and were more likely to be euthanized than dogs in the general population. Based on previous research and this study’s findings, the authors recommend that shelters discontinue the food guarding assessment. ABSTRACT: Many shelters euthanize or restrict adoptions for dogs that exhibit food guarding while in the animal shelter. However, previous research showed that only half the dogs exhibiting food guarding during an assessment food guard in the home. So, dogs are often misidentified as future food guarders during shelter assessments. We examined the impact of shelters omitting food guarding assessments. Nine shelters conducted a two-month baseline period of assessing for food guarding followed by a two-month investigative period during which they omitted the food guarding assessment. Dogs that guarded their food during a standardized assessment were less likely to be adopted, had a longer shelter stay, and were more likely to be euthanized. When the shelters stopped assessing for food guarding, there was no significant difference in the rate of returns of food guarding dogs, even though more dogs were adopted because fewer were identified with food guarding behavior. Additionally, the number of injuries to staff, volunteers, and adopters was low (104 incidents from a total of 14,180 dogs) and did not change when the food guarding assessment was omitted. These results support a recommendation that shelters discontinue the food guarding assessment.